Rôles of Surface Factor and a Plasma Inhibitory Activity (Anti-SF) During Experimental Thrombosis in Rabbits - Iatridis, S. G; Iatridis, P. G; Ferguson, J. H (Thrombosis and Haemostasis, 1964)
Intravenous injection of active surface factor (SF) preparations, in rabbits, induces a thrombotic tendency, which correlates with a hypercoagulability of the blood revealed with the thrombelastograph. These effects are largely dissipated within 10 minutes post-injection. Portal vein injections, or confirmed occlusion of the liver circulation, fail to show that the SF inactivation has any direct connection with the liver. Rabbit plasma normally contains a high titer of inhibitor (anti-SF), which shows no significant increase after the SF injections. The inhibition is chiefly “progressive” in rabbit plasma. Plasma anti-SF could largely explain the nonpersistence of hypercoagulability and thrombo-genic activity in the 10 min post-injection tests. These mechanisms may be an important element in the body defenses against any thrombotic tendency associated with increased SF activity.